Strategi BPRS Mitra Mentari Sejahtera dalam Meningkatkan Minat Pelajar untuk Menabung di Tabungan Simpel Ib (Simpanan Pelajar) - Nilam Nurylawati; Nurma Fitrianna (Falahiya: Journal of Islamic Banking and Finance, 2024)
Introduction: Bank strategy is a planning and management to achieve certain goals carried out by bussiness entities to collect funds from the public in the form of savings and channel them to the community in the form of financing to improve people’s lives. The main objective of this study in to analyze the strategy of BPRS Mitra Mentari Sejahtera in increasing students’ interest saving, secondly to analyze the factors influencing students’ interest in using Simpel iB saving, and thirdly to analyze the effectiviness of the strategy implemented by BPRS Mitra Mentari Sejahtera in increasing student interest.to save. Research Methods: This type of research is field research with a qualitative approach. As for the data collection techniques of observation, interviews and docummentation. The analysis used uses the inductive method, namely a method that draws conclusions based on these observations. Result:The results of the study show that: 1) The strategies used by BPRS Mitra Mentari Sejahtera in creasing students’ interest in saving using the 4P Marketing Mix are, Product, Price, Place, and Promotion. However, of the 4P, the most frequently used are promotions with direct socialization using bank sarvice cars (ball pick-up systems) and inderect socialization (print and online media). 2) factors that influence students’ interest in saving are internal and external factors. Internal factors are factors from within ourselves, namely factors needs and desires. While external factors are factors that are influenced from outside, namely culture and environment. 3) The effectiveness of the strategy implemented by BPRS Mitra Mentari Sejahtera increasing students’ interst in saving can be said to be effective with a system implemented in the form of outreach.